What do future physicians think of traditional, complementary, and integrative medicine (TCIM)? Fifteen years after the inclusion of TCIM in the Swiss constitution - Ilana Berlowitz; Helena Adler; Daniel Gallego Perez; Arnoud J. Templeton; Ursula Wolf (PLoS ONE, 2025)
Background An increasing recognition of traditional, complementary and integrative medicines’ (TCIM) contributions for public health has driven the development of international policy recommendations for its inclusion into national healthcare systems. While many countries have made advances in the incorporation of TCIM in academic medicine, there are globally only a handful that have a constitutional mandate in this context. The present cross-sectional study focused on one of these, namely Switzerland, some fifteen years after TCIM was included into the country’s Federal Constitution. Aims & methods This research aimed to examine attitudes of the future medical workforce in regard to TCIM within the only European country in which TCIM is mandated by the constitution. More specifically, using an online survey tailored to the country’s socio-political context, this study assessed attitudes, knowledge, and expectancies regarding TCIM among medical students across all Swiss universities that offer degrees in human medicine. Results Even though Swiss medical schools have consolidated and expanded their TCIM-related curricula compared to earlier assessments, with all of them now offering mandatory TCIM classes, most participants were unaware of this. Nonetheless, two-thirds of the N = 695 participants considered TCIM a valuable extension of conventional medicine that should have a place in medical education. Views diverged greatly between TCIM modalities. Further, we found significant differences as a function of gender and linguistic regions, although in the latter case effect sizes were modest. Conclusions Knowing the views of medical students as the future generation of physicians, clinical scientists, and often also decision-makers in the context of policy-driven integration is crucial in understanding the future trajectory of TCIM into mainstream healthcare. Based on Switzerland’s unique experience and history in this context this work contributes to the broader discourse on the role of TCIM in national healthcare systems.